CircEpha5 regulates the synthesis and secretion of androgen in mouse preantral follicles by targeting miR-758-5p - Xueying Zhang; Jiaxuan Liu; Hao Wu; Yan Chen; Xuesen Zhang; Boqun Xu (Taylor & Francis Group, 2023)
Circular RNAs are involved in the pathogenesis of various diseases, although its expression pattern and role in polycystic ovary syndrome (PCOS), characterised by hyperandrogenism, are not very clear. This article assessed the circRNAs expression profile in the ovaries of PCOS mice by circRNAs high-throughput sequencing and explored the role of circEpha5 in hyperandrogenism. The results showed that the overexpression of circEpha5 in mouse preantral follicles could increase the expression of Cyp17a1, an androgen synthesis-related gene, which resulted in a higher serum level of testosterone. Dual-luciferase reporter gene studies identified miR-758-5p as a direct target of circEpha5. Consequently, miR-758-5p expression was downregulated upon circEpha5 overexpression. Ectopically expressed miR-758-5p reversed the stimulation effects of circEpha5 on steroidogenesis-related gene expression and testosterone release. Therefore, circEpha5 could sponge miR-758-5p to regulate the expression of Cyp17a1, thereby promoting the synthesis and secretion of androgen in the preantral follicles. This work is contributed to the understanding of the pathogenesis of hyperandrogenemia and lays the foundation for the development of therapeutic targets of PCOS hyperandrogenism.